PERILAKU TENAGA KESEHATAN DALAM MEMBERIKAN PENDIDIKAN KESEHATAN DENGAN PERILAKU IBU DALAM PEMBERIAN KAPSUL VITAMIN A PADA ANAK BERUSIA 6 – 59 BULAN - Herawati; Nurlatifah; Mohammad, Basit (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
Coverage of capsule vitamin A as supplementation on children under five years of age is still belowstandard. One effective way of doing increase capsule vitamin A supplementation is to steer theprocess of implementing or improving the success of this activity. It can also involve health workersand cadres to provide counseling regarding the intake of capsule vitamin A that families can bemotivated in the fulfillment of vitamin A. This study aimed to determine the correlation of healtheducation with mother behaviour of giving capsule vitamin A in children age 6-59 months at thehealth center Kelayan Dalam Banjarmasin. This study used a correlational research design to testthe correlation between variables. The type of research using cross sectional with 55 sample taken atpurposive sampling. Data was collected using a questionnaire. Data were analyzed using SpearmanRank correlation with significant value of p <0.05. The results showed that the health education havebeen associated with mother behavior ofgiving capsule vitamin A for children age of 6-59 months atPuskesmas Kelayan Dalam Banjarmasin with significant value p = 0.001 (less than 0.05) and thecorrelation coefficient = 0.419. There was a significant correlation between the health education havebeen associated with mother behavior ofgiving capsule vitamin A for children age of 6-59 months atthe Health Center Kelayan Dalam Banjarmasin.